Proses Implementasi Managemen Kualitas - Rahmana, Arief; Sunaryo, Indryati; Irianto, Dradjad; Hidajat, Ubuh Buchara (Jurnal Teknik Industri, 2010)
Study of The Implementation Process of Quality Management (Case Study Research In Company X). This research is carried out to study implementation process of quality management,which consists of three stages namely introduction, adoption, and adaptation. Research strategy in this research is case study research in Company X, which is a company that already has the ability to export and certified quality assurace system. Prime method of collecting data is structured interview with director, managers, supervisors, and employees Company X. The result indicate that in the introduction stage are shown by customer recognition of quality product, Company X began to export, and demand of foreign customer to quality assurance system. In the adoption stage are shown by company’s plan for certification of quality assurance system, certification of quality assurance system, and quality improvement. Meanwhile, in the adaptation stage are shown by recertification of quality assurance system, upgrading of quality assurance system,and production process evaluation. Those result give insight that Company X has carried out continuous quality improvement through quality management implementation with the aim to enhance customer satisfaction.